Herman's stages of recovery on characters with a traumatic past in Yejide Kilanko's Daughters Who Walk This Path - Namasivayam, Shalini; Noor, Rohimmi (Universiti Putra Malaysia Press, 2017)
In general, trauma is often a threat to life when it involves physical harm. However, an overwhelming feeling can also be traumatic. Recovery, on the other hand, is the process in which characters manage to restore their life back to normal. The main focus of this study is to examine the types of trauma and the stages of recovery that characters in the selected novel go through by using Judith Herman’s concepts of Trauma and Recovery. The main concept of Trauma that will be analysed in this study is child abuse while the stages of recovery to be discussed include reconnection and the dialectic of continued trauma. The study examines these issues in the narrative of Daughters Who Walk This Path, written by Yejide Kilanko. This novel depicts ill-fated events that eventually lead to the characters’ traumatic experience and later the recuperation that the characters go through. Daughters Who Walk This Path portrays how a traumatised rape victim manages to move on with life after that torture. The book portrays how the traumatised characters managed to recover from their dark past in order to live a normal life.